2011
DOI: 10.1177/000313481107700716
|View full text |Cite
|
Sign up to set email alerts
|

The Component Separation Technique for Hernia Repair: A Comparison of Open and Endoscopic Techniques

Abstract: The open components separation technique (CST) for hernia repair allows for autologous tissue repair with approximation of the midline fascia in patients with complex hernias. CST requires creation of large undermining skin flaps, whereas the endoscopic component separation technique (ECST) is performed without division of the epigastric perforating vessels and may minimize wound morbidity. A review of patient demographics and outcome measures of patients undergoing CST and ECST between November 2008 and Febru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
17
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(19 citation statements)
references
References 14 publications
(21 reference statements)
1
17
0
1
Order By: Relevance
“…On pairwise meta-analysis, primary fascial closure was associated with lower odds of SSO and recurrence than bridged repair (Table 4) [23][24][25][26][27][28]. The heterogeneity p value was 0.229 for SSO, indicating no statistically significant heterogeneity; however, the heterogeneity p value for recurrence was 0.012, suggesting heterogeneity of the studies.…”
Section: Part IImentioning
confidence: 99%
“…On pairwise meta-analysis, primary fascial closure was associated with lower odds of SSO and recurrence than bridged repair (Table 4) [23][24][25][26][27][28]. The heterogeneity p value was 0.229 for SSO, indicating no statistically significant heterogeneity; however, the heterogeneity p value for recurrence was 0.012, suggesting heterogeneity of the studies.…”
Section: Part IImentioning
confidence: 99%
“…Some of the results are case presentations and some are technical discussions; studies related to this new technique are still very scarce. As in our study, 8 studies in the literature survey compared conventional and endoscopic CST in treating uncommon GVIHs [15,[20][21][22][23][24][25][26]. One is a study that mainly emphasizes both methods in terms of cost [25].…”
Section: Discussionmentioning
confidence: 89%
“…Both groups were also compared in terms of postoperative complications; there was no statistically significant difference between them (P = 0.656). Many studies have reported that the greatest advantage of the endoscopic method compared with the conventional method is a reduction in postoperative complications, especially related to the wound site [15,20,[22][23][24][25][26], but Azoury et al found no significant difference in postoperative complications between the methods. We also did not find this advantage of the endoscopic procedure to be statistically significant in our study.…”
Section: Discussionmentioning
confidence: 99%
“…There was a significantly higher rate of contaminated or infected wounds in the open group of Giurgius et al [18] (33% vs. 5%, p=.03). Albright et al [16] also contained a much higher percentage of contaminated cases in the open group although this result was not statistically significant (35.7% vs. 9.1%, p=NS). A subgroup analysis was performed by both authors for patients with only clean wounds in each group.…”
Section: Wound Complicationsmentioning
confidence: 89%
“…A major issue with open component separation is its high wound complication rate [6][7][8][9]. All studies comparing open to endoscopic component separation demonstrated a trend toward decreased wound complications in the endoscopic group [14][15][16][17][18], although only two, Albright et al [16] and Giurgius et al [18], were able to achieve statistical significance. In both studies, patients were not adequately matched in terms of preoperative wound contamination.…”
Section: Wound Complicationsmentioning
confidence: 99%